Podejście procesowe w specyfikacji wymagań użytkowników - Marcinkiewicz, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Specification (Elicitation) and Analysis of user requirements is a critical part of development process of information system. It is separated as specific domain of research and professional activities called "Requirements engineering". Requirements engineering proposes different approaches to requirements specifications. A process oriented approach is one of the approaches of this kind. Its importance progresses with generalization of business process modernization in enterprises. There are three parts of this paper. The first is a review of essentials techniques of requirements specifications. The next presents possibilities of Unified Modeling Language (UML) to specify u requirements by modeling business process. The last part contains a description of foundations о process oriented method, which can be used for specification of user requirements specifications. This method joins object and process approach in requirements engineering. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 208-222